Electronic Oxide–Metal Strong Interaction (EOMSI). Issue 60 (17th September 2020) - Qian, Kun; Duan, Huimei; Li, Yangyang; Huang, Weixin
Abstract: Strong metal–support interaction of supported metal catalysts is an important concept to describe the effect of metal–support interactions on the structures and catalytic performances of supported metal particles. By using an example of CeO x adlayers supported on Ag nanocrystals, herein a concept of electronic oxide–metal strong interaction (EOMSI) is put forward; this interaction significantly affects the electronic structures of oxide adlayers through metal‐to‐oxide charge transfer. The EOMSI can stabilize oxide adlayers in a low oxidation state under ambient conditions, which individually are not stable; moreover, the oxide adlayers experiencing the EOMSI are resistant to high‐temperature oxidation in air to a certain extent. Such an EOMSI concept helps to generalize the strong influence of oxide–metal interactions on the structures and catalytic performance of oxide/metal inverse catalysts, which have been attracting increasing attention. Abstract : Electronic oxide–metal strong interactions (EOMSIs) can exist in oxide/metal inverse catalysts thanks to metal‐to‐oxide charge transfer stabilizing oxide adlayers in a low oxidation state, which individually are not stable under ambient conditions, from being oxidized at high temperatures to a certain extent.